Blended learning and online tutoring : planning learner support and activity design - MacDonald, Janet (Gower, 2008)
This book adopts a pragmatic and commonsense approach to blended learning by situating the use of online media within a well-grounded teaching and learning strategy. It provides practical ideas for the successful implementation of blended strategies, including good practice in both asynchronous and synchronous tutoring, appropriate assessment design for developing successful blended learners, and innovative approaches to professional development for distance tutors. It is illustrated with a wide